[The Social Rate of Discount and the Optimal Rate of Investment]: Further Comment - Lind, Robert C. (Quarterly Journal of Economics, 1964)
Journal Article Further Comment Get access Robert C. Lind Robert C. Lind Stanford University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 78, Issue 2, May 1964, Pages 336–345, https://doi.org/10.2307/1879333 Published: 01 May 1964